Searching for a better life : growing up in the slums of Bangkok - Mahony, Sorcha (Berghahn Books, 2018)
"Life in Bangkok for young people is marked by profound, interlocking changes and transitions. This book offers an ethnographic account of growing up in the city's slums, struggling to get by in a rapidly developing and globalizing economy and trying to fulfill one's dreams. At the same time, it reflects on the issue of agency, exploring its negative potential when exercised by young people living under severe structural constraint. It offers an antidote to neoliberal ideas around personal responsibility, and the assumed potential for individuals to break through structures of constraint in any sustained way"--